Natural History Observations on a Warty Frog: Callulina dawida (Amphibia: Brevicipitidae) in the Taita Hills, Kenya. (15th March 2012) - Malonza, Patrick K.
Abstract : Amphibian populations are declining throughout the world, but most of the susceptible species possess particular biological attributes. Understanding these traits plus the environmental factors responsible for declines greatly aids conservation prioritization and planning. This paper examines the natural history observations and ecological characteristics of Callulina dawida, a frog endemic to the montane forests of the Taita Hills, Kenya. Sampling was accomplished by use of standardized pitfall trapping, transects, and time-limited searches. Mean monthly temperature and elevation significantly influenced the species distribution and abundance but mean monthly rainfall did not. The species was rare or absent during the cold season and its abundance increased with elevation. Breeding occurred during the long dry season (June to October) with juveniles being abundant between January and March. Available evidence shows that this species deposits a cluster of large yolk-rich eggs on the forest floor with maternal care and direct development. Its occurrence only within highly fragmented indigenous forests makes the species worth listing as critically endangered. To conserve this species, all remaining indigenous forest fragments including those communally or privately owned should be preserved and connected through planting of indigenous trees along stream valleys. In addition, the exotic tree plantations should be replaced with indigenous trees to restore the species habitat.